2019
DOI: 10.1002/jsde.12313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Divalent Salts on the Interfacial Activity of the Mixed Surfactants at the Water/Model Oil Interface

Abstract: In our previous report, the mixed cationic/anionic surfactant system consisting of N‐dodecyl‐N‐methylpyrrolidinium bromide (L12) and sodium dodecyl sulfate (SDS) showed good interfacial tension (IFT) reduction of water/model oil (Vtoluene:V n‐decane = 1:1). In the present study, the effects of divalent salts (MgCl2 or CaCl2) on the interfacial activity were systematically evaluated. The additional Mg2+ ions greatly reduced the IFT to an ultralow value, whereas Ca2+ ions caused the generation of the precipitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…The first model oil (model oil A) was prepared by adding 10,000 ppm of stearic acid into the base oil. The second model oil (model oil B) was prepared by adding 10,000 ppm of n -decylamine in the base oil. Moreover, during contact angle measurement, a small amount of oil-soluble dye (Sudan Black) was mixed with model oils to add color to the transparent model oil phase for better visibility during contact angle studies.…”
Section: Methodsmentioning
confidence: 99%
“…The first model oil (model oil A) was prepared by adding 10,000 ppm of stearic acid into the base oil. The second model oil (model oil B) was prepared by adding 10,000 ppm of n -decylamine in the base oil. Moreover, during contact angle measurement, a small amount of oil-soluble dye (Sudan Black) was mixed with model oils to add color to the transparent model oil phase for better visibility during contact angle studies.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the synergistic effect of Mg 2+ on surfactants has been reported in many studies. [38][39][40][41] Combined with the significant increase of the zeta potential of the mixed system caused by a small amount of Ca 2+ , it can be preliminarily speculated that there is another stronger interaction between Mg 2+ /Ca 2+ and AE 7 C-Na/ ADQ-12 except the electrostatic interaction which forces metal ions and mixed surfactants to form new complexes.…”
Section: Characterization Of Surface Activity and Solution Stabilitymentioning
confidence: 99%
“…Davis et al found that the addition of Na + reduced the electrostatic repulsion force of the anionic surfactant and allowed the surfactant to accumulate more closely on the oil–water interface, enhancing the stability of O/W emulsions stabilized by sodium lauryl ether sulfate. Compared with monovalent ions, divalent ions, such as calcium ions (Ca 2+ ) and magnesium ions (Mg 2+ ), have more significant effects on the emulsion stability, which may be attributed to the difference in the chemical structure and valence state. Kazemzadeh et al pointed out that the interaction of asphaltene with Ca 2+ and Mg 2+ in the water phase caused a more stable water-in-crude oil emulsion, which resulted in droplets with a smaller average area and a lower value of interfacial tension . Previous studies have mainly been focused on the effects of monovalent and divalent cations on the stability of emulsions stabilized by different emulsifiers.…”
Section: Introductionmentioning
confidence: 99%